Land Use Policies and Tenure in Economic Liberalization Regime: Land Law in Agro-Industrial Context - Aris Yulia; Fatma Ayu Jati Putri; Erna Wati (Lex Publica, 2023)
Abstract. The Basic Agrarian Law (BAL) in Indonesia serves as the constitutional foundation for ensuring state control over land, water, and natural resources for the collective welfare of its people. However, the growth of capitalism and the free-market system has had a significant impact on land tenure and utilization by corporations in the country. This paper explores the consequences of economic liberalization, the role of foreign investment, and the resulting disparities between large corporations and local communities in land ownership. It also delves into the need for a balanced legal framework that prioritizes social justice, with a focus on equitable land use that benefits both industries and the broader community. The study adopts a socio-legal research approach to comprehend the practical implications of legal systems in society. By highlighting the interconnectedness of land, humanity, and the divine, and emphasizing Pancasila principles, the findings propose strategies to achieve a harmonious balance between corporate interests and community welfare.   Abstrak. Undang-Undang Pokok Agraria di Indonesia memiliki peran penting sebagai landasan konstitusional untuk memastikan penguasaan negara terhadap tanah, air, dan sumber daya alam demi kesejahteraan bersama rakyatnya. Namun, perkembangan kapitalisme dan sistem pasar bebas telah memberikan dampak yang signifikan terhadap penguasaan dan pemanfaatan tanah oleh perusahaan di negara ini. Tulisan ini menjelajahi akibat dari liberalisasi ekonomi, peran investasi asing, serta kesenjangan yang muncul antara perusahaan besar dan komunitas lokal dalam kepemilikan tanah. Selain itu, kami juga akan menggali tentang perlunya kerangka hukum yang seimbang dengan fokus pada keadilan sosial, dan bagaimana pemanfaatan tanah yang adil dapat memberi manfaat bagi baik industri maupun masyarakat luas. Penelitian ini menggunakan pendekatan sosial-legal untuk memahami dampak nyata dari sistem hukum dalam masyarakat. Dengan menyoroti keterkaitan antara tanah, kemanusiaan, dan hal yang Ilahi, serta menekankan prinsip-prinsip Pancasila, penelitian ini akan menyajikan strategi untuk mencapai keseimbangan harmonis antara kepentingan korporasi dan kesejahteraan masyarakat. Kata kunci: Hukum pertanahan, Tata guna lahan, Kepemilikan lahan, Liberalisasi ekonomi, Indonesia